Evaluation of Transparency and Accountability of Regional Government Financial Reports in the Digitalization Era - Yesbarianus Parindingan, Frivaldo; Haliah, Haliah; Nirwana, Nirwana (Journal of Accounting and Finance Management, 2024)
The research findings indicate that the most frequently studied variables over the past decade, Transparency and accountability are associated with participation, good governance, and corruption. Transparency and accountability are the most important principles in achieving good governance and preventing bad governance. Public participation plays a crucial role as a mechanism to review and monitor government performance , particularly in the context of corruption prevention . The consistent development of these topics, as demonstrated by the research, suggests that transparency and accountability remain relevant and evolving areas of study. This continuous evolution makes these themes highly intriguing for future research, especially in examining how they interrelate with governance practices, public participation, and efforts to combat corruption. The dynamic nature of these topics provides opportunities to explore new frameworks and approaches in addressing challenges within public governance systems